Ultrahigh thermoelectric power factor in flexible hybrid inorganic-organic superlattice. Issue 1 (December 2017) - Wan, Chunlei; Tian, Ruoming; Kondou, Mami; Yang, Ronggui; Zong, Pengan; Koumoto, Kunihito
Abstract Hybrid inorganic–organic superlattice with an electron-transmitting but phonon-blocking structure has emerged as a promising flexible thin film thermoelectric material. However, the substantial challenge in optimizing carrier concentration without disrupting the superlattice structure prevents further improvement of the thermoelectric performance. Here we demonstrate a strategy for carrier optimization in a hybrid inorganic–organic superlattice of TiS2 [tetrabutylammonium]x [hexylammonium]y, where the organic layers are composed of a random mixture of tetrabutylammonium and hexylammonium molecules. By vacuum heating the hybrid materials at an intermediate temperature, the hexylammonium molecules with a lower boiling point are selectively de-intercalated, which reduces the electron density due to the requirement of electroneutrality. The tetrabutylammonium molecules with a higher boiling point remain to support and stabilize the superlattice structure. The carrier concentration can thus be effectively reduced, resulting in a remarkably high power factor of 904 µW m−1 K−2 at 300 K for flexible thermoelectrics, approaching the values achieved in conventional inorganic semiconductors. Hybrid inorganic-organic superlattices show promise for flexible thermoelectric applications, yet they suffer from limited performance. Here, the authors devise a strategy for carrier optimization in a hybrid inorganic-organic superlattice of TiS2 [tetrabutylammonium]x [hexylammonium]y, achieving an ultrahigh power factor of 904 μW m−1 K−2 .